Meningkatkan Motorik Halus Melalui Kegiatan Mewarnai Menggunakan Media Alam Pada Anak Usia 5-6 Tahun Kober Raudhatul Jannah Karangtengah Garut - Jubaedah, Siti; Kurniawaty, Lia; Hamidah, Agustin (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research aims to improve fine motor skills of young children through coloring activities. Fine motor skills are an important aspect of a child's development that involves the coordination of small muscles in the hands and fingers. Coloring activities were chosen because they are believed to stimulate and improve these skills in a fun and interactive way. The research method used is the classroom action research method. The research subjects consisted of 14 children aged 5 -6. Data was collected using observation sheets and fine motor skills tests before and after intervention. The results of the research showed that there was a significant increase from the beginning of the pre-cycle with an average value of 44.6%, then there was an increase in cycle I with a value of 53%, continuing to cycle II 81.3% and there was also an increase.